PRN Medicines Management for Older People with Long-Term Mental Health Disorders in Home Care - Vaismoradi M; Jamshed S; Lorenzl S; Paal P (Dove Medical Press, 2021)
Mojtaba Vaismoradi,1 Shazia Jamshed,2 Stefan Lorenzl,3,4 Piret Paal5 1Faculty of Nursing and Health Sciences, Nord University, Bodø, 8049, Norway; 2Clinical Pharmacy and Practice, Faculty of Pharmacy, University Sultan Zainal Abidin, Terengganu, 22200, Malaysia; 3Professorship for Palliative Care, Institute of Nursing Science and -Practice, Paracelsus Medical University, Salzburg, 5020, Austria; 4Department of Neurology, Klinikum Agatharied, Hausham, 83734, Germany; 5WHO Collaborating Centre at the Institute for Nursing Science and Practice, Paracelsus Medical University, Salzburg, A-5020, AustriaCorrespondence: Mojtaba VaismoradiFaculty of Nursing and Health Sciences, Nord University, Bodø, 8049, NorwayTel +47 75 51 78 13Email mojtaba.vaismoradi@nord.noAbstract: Older people with long-term mental health conditions who receive care in their own home are vulnerable to the inappropriate use of medications and polypharmacy given their underlying health conditions and comorbidities. Inappropriate use of pro re nata (PRN) medications in these older people can enhance their suffering and have negative consequences for their quality of life and well-being, leading to readmission to healthcare settings and the increased cost of health care. This narrative review on published international literature aims at improving our understanding of medicines management in home care and how to improve PRN medication use among older people with long-term health conditions in their own home. Accordingly, the improvement of PRN medicines management for these older people requires the development of an individualised care plan considering 'reduction of older people's dependence on PRN medications', 'empowerment of family caregivers', and 'support by healthcare professionals.' PRN medication use should be reduced through deprescription and discontinuation strategies. Also, older people and their family caregivers should be encouraged to prioritize the use of non-pharmacologic methods to relieve physical and psychological problems. Besides the empowerment of family caregivers through role development, education and training about PRN medications, and involvement in decision-making, they need support by the multidisciplinary network in terms of supervision, monitoring, and home visits.Keywords: family caregiver, home care, medication, medicines management, mental health, older people, patient safety, pro re nata, PRN